Proceedings of the 15th International Symposium on Management (INSYMA 2018) 2018
DOI: 10.2991/insyma-18.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Javanese lunar calendar effect (Primbon) on abnormal return

Abstract: The purpose of this study is to examine Javanese lunar calendar (Primbon) effect to abnormal return on Indonesian Stock Market. Type of this study is conclusive descriptive using intraday trading data. The research observed and tested cultural phenomena called Primbon as a calendar effect on abnormal return. Studies of cultural event, Ramadhan effect. This research examined other issues which is a belief of traditional calendar called Primbon among Javanese in Indonesia. This study uses event study methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The results of this research also discovered that the month of Sela might shape investor behavior due to cultural influences (Al-Ississ, 2015;Wasiuzzaman & Al-Musehel, 2017;Zhan, 2019). If there is a change in investor behavior, many investors tend to take various actions to gain profits on the capital market (Hermin & Mahadwartha, 2018;Liu, 2013;Robiyanto & Puryandani, 2015), which can cause a difference in returns in the months of Sela, Sawal, and Besar.…”
Section: Table 2 Garch (11) Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…The results of this research also discovered that the month of Sela might shape investor behavior due to cultural influences (Al-Ississ, 2015;Wasiuzzaman & Al-Musehel, 2017;Zhan, 2019). If there is a change in investor behavior, many investors tend to take various actions to gain profits on the capital market (Hermin & Mahadwartha, 2018;Liu, 2013;Robiyanto & Puryandani, 2015), which can cause a difference in returns in the months of Sela, Sawal, and Besar.…”
Section: Table 2 Garch (11) Resultsmentioning
confidence: 62%
“…The uniqueness of this research is that it examines the phenomenon of the month of Sela in the Javanese calendar. Previous research has found that there was no effect of the Javanese calendar (Robiyanto & Puryandani, 2015), but there were also those who discovered a partial effect of the Javanese calendar on returns in Indonesia (Hermin & Mahadwartha, 2018). However, the previous research was based on the days in the Javanese calendar, which are referred to as "pasaran", and not based on the months, so further research on the effects of the Javanese calendar, which is based on the months, is quite crucial.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations